Preparation and evaluation of atrazine immunoconjugate - Riccardi, Carla dos Santos; Araújo, Ângela Regina; Yamanaka, Hideko (Eclética Química, 2002)
In order to study the affinity reaction between the anti-atrazine antibody and atrazine, an enzyme was incorporated, as a marker, to an atrazine carboxylic derivative. The hapten and conjugate were synthesized and characterized by MS, IR and NMR. The interaction between monoclonal antibodies and hapten-HRP conjugate was investigated by enzyme linked immunosorbent assay (ELISA).